Soul, impulse, and movement according to Alexander of Aphrodisias - Vigo, Alejandro G. (Estudios de Filosofía, 2009)
this paper discusses Alexander of Aphrodisias’ conception of the soul, paying special attention to a specific aspect distinguishing the Alexandrian view from the Aristotelian one: the impulsive capacity or faculty. Firstly, it considers Alexander’s reformulation of Aristotle’s approach to the soul (as a form of the body), a reformulation that is performed in connection with his original reconstruction of hilemorphism. At this point the author makes a special emphasis upon the manner Alexander develops a ‘terraced model’ of hilemorphic composition. Secondly, the treatment of impulsive faculty, with a special focus on the theoretical performance that Alexander derives from taking the notion of impulse, is developed. Finally, Alexander’s reformulation of the Aristotelian psychology of action is also brie y considered in order to account for the sequence of the process of the production of voluntary movement and of action. This is an explicative model that leaves aside the Aristotelian resource to the structure of the practical syllogism, and incorporates the elements predominantly characteristic of the Stoic conception. This, though, does not entail the abandonment of the basic thesis of Aristotle’s stance regarding motivation, as an opposition to socratic intellectualism: the thesis of the primacy of desire, in all its possible ways, as a factor accounting for the origin of voluntary movement and action.